Psychotherapy for mental health symptoms and disorders in elite athletes: a narrative review - Stillman, M. A.; Glick, I. D.; McDuff, D.; Reardon, C. L.; Hitchcock, M. E.; Fitch, V. M.; Hainline, B. (British Journal of Sports Medicine, 2019)
Background: Athletes, like non-athletes, suffer from mental health symptoms and disorders that affect their lives and their performance. Psychotherapy, either as the sole treatment or combined with other non-pharmacological and pharmacological strategies, is a pivotal component of management of mental health symptoms and disorders in elite athletes. Psychotherapy takes the form of individual, couples/family or group therapy and should address athlete-specific issues while being embraced as normative by athletes and their core stakeholders.